2009
DOI: 10.1111/j.1540-8159.2009.02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Adenosine Triphosphate with a Sufficient Observation Period for Detecting Reconduction after Pulmonary Vein Isolation

Abstract: A sufficient observation period and the use of ATP are useful to detect early reconduction after PV isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Although adenosine may have similar effects during the adrenergic rebound phase that follows its administration, it may also unmask the potential for conduction recovery by hyperpolarizing cells in partially ablated tissue. While adenosine or other purinergic agonists have been used to reveal dormant pulmonary vein (PV) conduction following electrical isolation for the treatment of atrial fibrillation, it has been incompletely studied after atrial flutter ablation. There are 3 recent small series that investigated whether adenosine could reveal dormant conduction in the CTI after atrial flutter ablation, but their results are conflicting .…”
Section: Introductionmentioning
confidence: 99%
“…Although adenosine may have similar effects during the adrenergic rebound phase that follows its administration, it may also unmask the potential for conduction recovery by hyperpolarizing cells in partially ablated tissue. While adenosine or other purinergic agonists have been used to reveal dormant pulmonary vein (PV) conduction following electrical isolation for the treatment of atrial fibrillation, it has been incompletely studied after atrial flutter ablation. There are 3 recent small series that investigated whether adenosine could reveal dormant conduction in the CTI after atrial flutter ablation, but their results are conflicting .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The equivalence/difference of the time-and ATP-dependent EPVR has been demonstrated to be moderate ( valueϭ0.50) by Jiang et al 18 Ninomiya et al also demonstrated that 40% of all reconduction (8 of 20 PVs) was detected with the use of ATP, while the remaining 60% appeared time dependently. 19 The mechanism by which ATP reveals the insufficiently ablated tissues was recently described by Datino et al They showed that ATP-induced hyperpolarization (through the increase of I KAdo ) restores excitability of PV muscle by removing voltage-dependent I Na inactivation. 20 …”
Section: Previous Studies For Epvrmentioning
confidence: 99%
“…9,10 Ninomiya et al found 12 and 8 PVs reconducted among a total of 81PVs with the combination of time-and ATP-induced provocation. 19 Although their study revealed a difference between the two methods of provoking PV reconnection, the end point to minimize the AF recurrence after the procedure remains unclear. This study attempted to induce EPVR repeatedly by the combination of time-and ATP-dependent provocation in order to establish a practical end point to minimize AF-recurrence after the PV isolation procedure.…”
Section: Combination Of Time-and Atp-dependent Provocation Of Epvrmentioning
confidence: 99%
“…One reason may be that ATP-induced dormant PV conduction was evaluated only in 566 PVs (78.8%). It has been shown that an APVR can be unmasked both ATP-dependently and time-dependently [19][20][21]31,32]. Another reason may be that the difference in the strategy used for PVI affected the incidence of APVR.…”
Section: Incidence Of Apvr During Pvimentioning
confidence: 93%